TRADITIONAL ASPECTS OF MODERN CLOTHES OF THE KARAKALPAK ETHNIC GROUPS OF FERGANA VALLEY (Scientific journal of the Fergana State University, 2023)
This article describes the traditional aspects of the clothes of the Karakalpak ethnic groups of Fergana Valley in historical and ethnographic terms. The process of integration of Uzbek and Karakalpak ethnocultural ties is compared.